Urban Grassland Management Implications for Soil C and N Dynamics: A Microbial Perspective - Thompson, Grant L.; Kao-Kniffin, Jenny (Frontiers in Ecology and Evolution, 2019)
Urban grasslands are turfgrass dominated landscapes of varying functions and uses that are ubiquitous in areas associated with human population growth and urbanization. While these landscapes are perceived to serve a primarily aesthetic function, they provide a multitude of beneficial ecosystem functions that impervious surfaces do not provide. Urban grassland soils have been shown to accumulate carbon (C) and nitrogen (N) for decades, matching native grasslands and eastern hardwood forest soils in terms of C and N densities. The establishment and maintenance of urban grasslands alters many microbially-mediated biogeochemical processes in soils, including soil organic matter (SOM) dynamics. Despite strong evidence of alterations to soil C and N cycling, the impacts of maintaining urban grasslands on soil microbiomes and their functions remain understudied compared to other ecosystems. Typical management practices can directly and indirectly affect edaphic factors in urban grasslands, which in turn, could impact soil processes mediated by microorganisms. We reviewed the existing literature on urban grassland management, focusing on how mowing, fertilization, irrigation, grass species composition, and soil cultivation could impact the composition and function of soil microorganisms. Although sparse, the literature indicates that the techniques used to maintain urban grassland habitats broadly select for copiotrophic microorganisms adapted to higher resource availability. Additionally, the studies indicate that greater soil fertility and plant productivity found in urban grasslands facilitate the accumulation of soil C and N, as well as SOM as compared to other land-use types. However, effects on soil biology and biogeochemistry depend on specific management practices, which are quite variable. Future research on soil C and N dynamics in urban grasslands should focus on the dominant component of this ecosystem—residential lawns—however, much of the existing scientific literature featuring turfgrass systems focus heavily on golf courses, athletic fields, and major tourist parks.